Identification of a site of psoralen crosslinking in E. coli 16S ribosomal RNA. - Turner, S (1982)
We have developed a 2-dimensional gel method for identification of RNA sequences crosslinked by the intercalative drug 4'-hydroxymethyl-4,5',8-trimethylpsoralen (HMT). This method is being used to localize such sites in E. coli ribosomal RNA. We report here the identification of a site for HMT crosslinking within positions 434 and 497 of 16S rRNA. We suggest a likely site for HMT intercalation, in which residues U548 and U473 become crosslinked via the drug.